HUBUNGAN INFEKSI MALARIA PADA IBU HAMIL DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH DI PUSKESMAS HARAPAN DISTRIK SENTANI TIMUR KABUPATEN JAYAPURA - Heni Voni Rerey; Romauli, Suryati; Dian Septiningsih Samber, Sisilia (Jurnal Medicare, 2025)
Malaria is still one of the health problems in several countries, including Indonesia. Malaria cases in pregnant women in Indonesia in 2019 were around 1,769 cases, the most in Papua Province. Pregnancy with malaria has an effect on low birth weight. The purpose of this study is to determine the relationship between malaria infection in pregnant women and the incidence of low birth weight (BBLR) at the Harapan Health Center, East Sentani District, Jayapura Regency. This type of research is quantitative with a case control design with a retrospective approach. The population is all pregnant women who live in the working area of the Harapan Health Center with a history of malaria in the last 2 (two) years, namely 2022-2023 with a sample of 77 respondents taken using the total sampling technique  according to the inclusion criteria. Data were obtained using questionnaires. The data was analyzed using the chi-square test (x2) using a significance level of 95%, for the closeness of the relationship was seen using the OR (odd ratio) value. The results of the study were obtained by most (72.7%) pregnant women aged 20-35 years, with secondary education (42.9%), not working (62.3%) with multigravida parity (68.8%), with a pregnancy gap of 2-5 years (53.2%). Most pregnant women are infected with malaria (74%) and give birth to babies with BBLR (54.5%). Bivariate analysis showed that there was a relationship between malaria infection and the incidence of BBLR with a value of p = 0.0000. The results of the OR test found that pregnant women infected with malaria were 12 times more likely to give birth to babies with BBLR.